2022
DOI: 10.3390/su14031904
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Effectiveness of Humanitarian Activities against COVID-19 Disruption: The Role of Blockchain-Enabled Digital Humanitarian Network (BT-DHN)

Abstract: The COVID-19 pandemic has affected more than 214 countries across the world, disrupting the supply of essential commodities. As the pandemic has spread, humanitarian activities (HAs) have attempted to manage the various situation but appear ineffective due to lack of collaboration and information sharing, inability to respond towards disruption, etc. This study aims to determine and provide insights into the critical factors that may enhance the effectiveness of HAs during the pandemic. A systematic literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 87 publications
0
12
0
Order By: Relevance
“…, 2016). Joshi et al. (2022) evaluate the key role of drones concerning global epidemics, including humanitarian relief for infectious diseases such as the Wuhan-COVID-19 crisis.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2016). Joshi et al. (2022) evaluate the key role of drones concerning global epidemics, including humanitarian relief for infectious diseases such as the Wuhan-COVID-19 crisis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Due to the multiple data sources, information overflows and thus needs digital technologies like big data to facilitate the humanitarian organizations (HOs) with real-time data to provide extended support to the affected areas during the disruption. Big data has changed the face of humanitarian operations in a much more effective manner by empowering actors through new-age technologies, including artificial intelligence (AI) (Roth and Luczak-Roesch, 2020; Sharma and Joshi, 2019; Joshi et al. , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the effective and efficient supply chain management improves the coordination between supply and demand by reducing costs (Ketokivi and Mahoney 2020 ). In addition, the challenges of supply chain management have further amplified with the Covid-19 pandemic (Hald and Coslugeanu 2021 ; Joshi et al 2022 ; Sharma et al 2021 ). Taking control over data is essential in this scenario as it allows to make decisions that can improve business performance.…”
Section: Introductionmentioning
confidence: 99%
“…Pagano et al ( 2019 ) developed a novel smart insurance contract to address the impact of natural hazards. In another study, Joshi et al ( 2022 ) explored the critical success factors for developing humanitarian activities during the COVID-19 pandemic. To achieve this, they used fuzzy DELPHI and DEMATEL.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this, they used fuzzy DELPHI and DEMATEL. Finally, they concluded that building a blockchain-based humanitarian network is the most significant critical factor (Choi et al 2019 ; Pagano et al 2019 ; Bryce et al 2020 ; Grima et al 2021 ; Joshi et al 2022 ). Fabri and Fabri ( 2019 ), Munawar et al ( 2022 ), Omar et al ( 2022 ), and Sahal et al ( 2022 ) stated that new research is needed to reveal how practically disruptive technologies, including BcT can be used to reduce disaster risk and improve resilience.…”
Section: Introductionmentioning
confidence: 99%